A Women and the World of Work Challenges in the Implementation of Labor Law: Perempuan dan Dunia Kerja: Tantangan dalam Implementasi Undang-Undang Ketenagakerjaan - Pradika Rakasiwy, Mochamad Randy; Surya Cipta, Viona Dea (Jurnal Administrasi Publik (JAP), 2025)
The transformation of labor law through the Job Creation Law has posed significant implementation challenges, particularly for female workers. This study aims to examine the psychological impacts of labor law enforcement inconsistencies on women workers by using a socio-legal and legal psychology approach. This qualitative descriptive research involved semi-structured interviews with seven female informants working in formal sectors in Surabaya. Findings reveal that the lack of compliance with maternity leave rights, gender-based discrimination, and unequal workloads have triggered psychological distress such as stress, anxiety, and decreased work motivation. On the other hand, positive practices from companies that properly implement labor regulations are shown to enhance workers’ psychological well-being. The study highlights the urgent need for stricter law enforcement, improved legal literacy, and an effective supervision system to ensure substantive justice for female workers.